Komunikasi Kelompok dalam Virtual Community - Wa Ode Nurhaliza; Nurul Fauziah (KOMUNIDA : Media Komunikasi dan Dakwah, 2020)
This study aims to analyze communication in virtual communities that are reviewed from a business, health and career-linkedIn perspective. This research uses the literature review method through literature search both books and international and national journals. The results showed that the virtual community was established and developed through Computer Mediated Communication (CMC) on various platforms. Virtual communities develop because individuals have the same goal. They bind themselves to join and exchange ideas, information in a virtual community because there are common motives and goals to be achieved. There are several similarities and differences that bind individuals to join virtual communities from a business, health and career-linked perspective. Trust and security are the main keys of individuals joined in virtual communication in various fields. In addition, in the business perspective, two reasons individuals join online trade are the use of a conducive community and virtual social environment. While in the context of health, the reason the community joins is the ease of accessing health information, trust and security of user data. Finally, in the context of career-linked development, individuals tie themselves into the community because this platform has advantages in forming social network capital, knowledge capital to form friendships. Virtual communities on various platforms (business, health and careers) continue to grow and are increasingly being asked by users. Keywords: community; social media; users; virtual